Voices that Weave Knowledge: A Biographical-Narrative and Hermeneutical-Critical Approach to Understanding the Experiential Knowledge of Rural Educators in the Department of Boyacá, Colombia - Cañón, Mónica Jacqueline Regalado; Morales, Julio César Ávila; Vargas, Hugo Hernando Mendoza (Journal of Posthumanism, 2025)
This article presents oral narrative as a central methodological strategy in the qualitative and critical-hermeneutic approach, highlighting its capacity to interpret and give meaning to human experiences in specific social and cultural contexts. Based on the experiences of four rural primary school educators of retirement age, a qualitative design was used that integrated the subjective voice of the participants, allowing for the joint construction of situated knowledge. The narrative not only facilitated the reconstruction of personal trajectories but also enabled a reflective dialogue between researchers and participants in an interpretive and circular process. The active role of the researcher and the richness of the context allowed for a deeper understanding of the explicit and implicit meanings of the life stories, shaping the research as a space for shared understanding and symbolic transformation.